The Use of Pocketbook For Increasing Knowledge and Motivation to Wear Dentures of Elderly in Timor-Leste - Soares, Idalina; Eldarita, Eldarita; Amanullah, Rizqi (Journal of Oral Health Care, 2023)
Background: The aspect of mindset of the elderly in Santa-Kruz, Nain-Feto, Dil, Timor-Leste, which considers the cause of tooth loss and the use of dentures is not important and some can be less concerned about oral and dental health, is one factor. Promotion of using pocketbooks to knowledge to increase the motivation of the elderly in the use of dentures. Objectives: To get to know the effectiveness of pocketbooks in increasing knowledge and motivation for the use of dentures. Methods: This study used a quasi-experiment, and the research design used a pre-test and post-test. The population in the study all elderly in Santa-Kruz District, Nain-Feto, Dili District, sample 70 people was taken total sampling technique. Questionnaire research instrument. Analysis results study using the statistical test Wilcoxon Signed Ranks Test. Results: Level of knowledge and motivation for using dentures before using pocketbooks with good (28.6%), medium (57.1%), and bad (14.3%) categories. Motivation is good (42.9%), moderate (28.6%), and bad (28.4%). After promotion with good (91.4%), bad (2.9%), bad 0. Good motivation (97.1%), moderate (2.9%), bad 0. Wilcoxon Signed Ranks Test analysis between the level of knowledge and motivation is a p-value (0.00) < (0.05), and the Mann-Whitney Test analysis between the level of knowledge and motivation is a p-value (0.00) < (0.05), from the results of this study shows the effectiveness of promotion using pocketbooks on knowledge about tooth loss and motivation for using dentures in the elderly. Conclusions: There was an increase in knowledge about tooth loss and motivation for using dentures after the promotion of using pocketbooks.